The PPN and motor control: Preclinical studies to deep brain stimulation for Parkinson’s disease - Lin, Caixia; Ridder, Margreet C.; Sah, Pankaj (Frontiers in Neural Circuits, 2023)
The Pedunculopontine nucleus (PPN) is the major part of the mesencephalic locomotor region (MLR), located in the is involved in the control of gait and locomotion. The PPN contains glutamatergic, cholinergic and GABAergic neurons that all make local connections, but also have long range ascending and descending connections. While initially thought of as a region only involved in gait and locomotion recent evidence is showing that this structure also participates in decision making to initiate movement. As a result, the PPN has been used as a target for Deep Brain Stimulation to manage freezing of gait in late Parkinson's disease. In this review we will discuss current thinking on the role of the PPN in locomotor control. We will focus on the cytoarchitecture and functional connectivity of the PPN in relationship to motor control.